Employability of young graduates in Europe. Issue 4 (1st July 2014) - Pavlin; Ivan Svetlik, Samo; Laetitia Garrouste, Christelle; Rodrigues, Margarida
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to measure the potential role of the field of education and the fact of having worked during studies on the employability of the higher educated (ISCED 5-6) cohort targeted by the ET2020 graduates' employability benchmark. Design/methodology/approach – Using the same data source as the benchmark (i.e. the annual LFS microdata from 2004 to 2010), and exploring the additional transition questions collected in the LFS 2009 ad hoc module, the authors define and test four hypotheses using a probit approach on each EU country. Findings – The degree plays a significant role in the employability of young graduates across countries and time. In terms of probability of employment, the leading field is health and welfare. In terms of type of contracts, the leading fields are social sciences and engineering. Moreover, what labour markets seem to value the most is the capacity of higher educated students to combine high-level studies and work, i.e. a high workload capacity and intellectual flexibility. Practical implications – Reaching the new European target of a minimum of 82 per cent of employment of young graduates will require countries to invest wisely in the most "employable" fields of education. This analysis will help policy makers in their future orientations towards that target. Originality/value – The originality of this work lies in its exploration of the exact same extraction of microdata used for the computation of the ET2020 Benchmark indictor and in its immediate political implications for the monitoring of this benchmark.